Sublethal Photodynamic Treatment Does Not Lead to Development of Resistance - Al-Mutairi, Rawan; Tovmasyan, Artak; Batinic-Haberle, Ines; Benov, Ludmil (Frontiers in Microbiology, 2018)
A promising new alternative approach for eradication of antibiotic-resistant strains is to expose microbes to photosensitizers, which upon illumination generate reactive oxygen species. Among the requirements for a potent, medically applicable photosensitizer, are high efficacy in killing microbes and low toxicity to the host. Since photodynamic treatment is based on production of reactive species which are potentially DNA damaging and mutagenic, it might be expected that under selective pressure, microbes would develop resistance. The aim of this study was to determine if antibacterial photodynamic treatment with a highly photoefficient photosensitizer, Zn(II) meso-tetrakis(N-n-hexylpyridinium-2-yl)porphyrin would lead to development of resistance. To answer that question, bacterial cultures were subjected to multiple cycles of sublethal photodynamic stress and regrowth, and to continuous growth under photodynamic exposure. Antibiotic-resistant S. aureus and E. coli clinical isolates were also tested for susceptibility to photodynamic inactivation and for development of resistance. Results demonstrated that multiple photodynamic exposures and regrowth of surviving cells or continuous growth under sublethal photodynamic conditions, did not lead to development of resistance to photosensitizers or to antibiotics. Antibiotic-resistant E. coli and S. aureus were as sensitive to photodynamic killing as were their antibiotic-sensitive counterparts and no changes in their sensitivity to antibiotics or to photodynamic inactivation after multiple cycles of photodynamic treatment and regrowth were observed. In conclusion, photosensitizers with high photodynamic antimicrobial efficiency can be used successfully for eradication of antibiotic-resistant bacterial strains without causing development of resistance.